2017
DOI: 10.1590/0001-3765201720150317
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Syzygium cumini leaves on laying hens performance and egg quality

Abstract: The aim of this study was to evaluate the effect of Syzygium cumini leaves (SCL) in laying hens diets on productive performance, egg quality and lipid oxidation of yolk. A total of 108 Hysex White laying hens were distributed in a completely randomized design with three treatments and six replicates of six birds each. The treatments consisted of SCL inclusion at dietary levels of 0, 5 and 10 g/kg. There was no significant effect of SCL inclusion on feed intake, laying percentage, weight and egg mass, feed conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Phytogenic can positively affect the health and productivity of poultry (13). Phytogenic can be herbs, whole plants, its parts, extracted, or essential oils from plants (14). Supplementation of essential oils from oregano, savory, and rosemary in diets can reduce ileal Lactobacillus spp., serum cholesterol concentration and increase meat oxidation stability (15).…”
Section: Discussionmentioning
confidence: 99%
“…Phytogenic can positively affect the health and productivity of poultry (13). Phytogenic can be herbs, whole plants, its parts, extracted, or essential oils from plants (14). Supplementation of essential oils from oregano, savory, and rosemary in diets can reduce ileal Lactobacillus spp., serum cholesterol concentration and increase meat oxidation stability (15).…”
Section: Discussionmentioning
confidence: 99%
“…Christaki et al [23] observed no major effect on egg traits of the quails fed with oregano, anise and olive leaves. Additionally, Freitas et al [27] observed no positive effect of Syzygium cumini which is a herb belongs the same family with myrtle (Myrtaceae) on egg weight and egg mass of laying hens. Yet in the present study, we found that the supplementation of laying hens with 2.5% of MPE improved egg weight.…”
Section: Discussionmentioning
confidence: 99%